Patterns of Action in Early Marriage: A Literature Review from Religious and Systems Theory Perspective - Akhmad Munib Siroj; Hanum Salsabila Arzhamalieva (Institut Studi Islam Muhammadiyah Pacitan, 2026)
Early marriage remains a complex social phenomenon influenced by cultural traditions, religious values, economic conditions, and social structures. This study aims to analyze the patterns of action underlying early marriage practices through the perspectives of social action theory, systems theory, and religion. The research employed a qualitative literature review method by analyzing scientific publications, books, journal articles, and research reports obtained from reputable databases such as Google Scholar, Scopus, and ScienceDirect. A total of 52 relevant sources published between 2015 and 2025 were selected through screening and thematic classification processes. The findings indicate that early marriage is predominantly driven by non-rational social actions, particularly affective and traditional actions shaped by emotions, customs, and social pressures. However, religion also functions as a form of value-oriented rationality, where marriage is viewed as a moral effort to avoid deviant behavior and preserve social values. From the perspective of Talcott Parsons’ systems theory, early marriage represents a mechanism of social adaptation, integration, goal attainment, and cultural maintenance within society. Meanwhile, Niklas Luhmann’s General Systems Theory explains that family systems create internal communication boundaries and agreements that legitimize early marriage practices. This study contributes theoretically by integrating social action theory, systems theory, and religious perspectives into a comprehensive framework for understanding early marriage as both an individual and systemic social phenomenon. The study recommends strengthening educational access, reproductive health literacy, and contextual religious understanding to reduce the prevalence of early marriage in contemporary society.